Structural Transformation of Small Farms in Moldova : Implications for Poverty Reduction and Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
The agricultural and food production sector plays a key role in fighting poverty and food insecurity in Moldova, but is facing critical challenges to modernize and integrate into the international market. This paper focuses on smallholder farms, which make up 95 percent of all farms, and explores their potential for growth and the poverty links. Findings reveal that structural change is slow and smallholder farm growth in Moldova is an exception, not the rule. Only a small share of smallholder farms have the interest or capacity to commercialize but need targeted support policies to grow, intensify their farm activities, and integrate into the markets. For the remaining majority, enhancing their livelihoods calls for policies beyond the agricultural sector to help farm households diversify toward non-farm income.